A fiber-based fluorometric system for in situ algal classification. (January 2016) - Zhang, Yilong; Liu, Le; Tao, Yi; He, Yonghong; Zhang, Pengfei; Cai, Zhonghua
Abstract: We develop a fast fiber-based in situ fluorescence system for phytoplankton taxonomy. The fluorescence is excited by high power LEDs with different wavelengths through a customized fiber bundle to the place of interest. Sinusoidal-amplitude-modulation (SAM) techniques are employed. The detection time is shorten to 0.1 s because the fluorescence is excited and demodulated by different wavelengths simultaneously. The fluorescence signal is demodulated by a digital lock-in amplifier. The device is tested in Shenzhen Bay, South China Sea. Highlights: A in-situ fluorometric system for algal classification is developed. An underwater probe without electronic components is devised. Samples of three different algae species have been classified quantitatively.